1978
DOI: 10.1111/j.1365-2141.1978.tb01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes in Myelofibrosis: a Possible Guide to Management

Abstract: Using a fluorescent technique intracellular immune complexes were found in the peripheral leucocytes in all of 12 patients with myelofibrosis studied. Fluorescent cells varied from 12% to 81%; with no relation to the total white count or any obvious clinical finding. Three of the patients with severe refractory anaemia benefited from immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…Thus, in the early phase of IMF the myeloproliferation may be accompanied by immune activity in the bone marrow with a marked increase of lymphoid nodules [54]. Furthermore, the favourable outcome of immunosuppressive therapy in MF-patients with biochemical evidence of autoimmune activity supports the involvement of autoimmune bone marrow damage in the development of myelofibrosis in a subgroup of patients [52,55].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, in the early phase of IMF the myeloproliferation may be accompanied by immune activity in the bone marrow with a marked increase of lymphoid nodules [54]. Furthermore, the favourable outcome of immunosuppressive therapy in MF-patients with biochemical evidence of autoimmune activity supports the involvement of autoimmune bone marrow damage in the development of myelofibrosis in a subgroup of patients [52,55].…”
Section: Discussionmentioning
confidence: 90%
“…Circulating immune complexes (CIC) and complement activation have been demonstrated [44,52,53], but the pathogenetic significance of these findings is uncertain, since the occurrence of CIC may solely reflect impaired clearance in the reticu-lymphocytic cells with ensuing impairment of both cellular and humoral immune reponses [60].…”
Section: Discussionmentioning
confidence: 99%
“…Since the severe refrac tory anemia of the patients responded to the treat ment, and immune complexes of our first patient dis appeared as in the study of Lewis and Pegrum [23], we believe that bolus treatment of méthylprednisolone was effective through its immunosuppressor effect, which should be shown by the study of other cases. More recently, Manoharan and Pitney [24] have shown that chemotherapy resolves symptoms and re verses marrow fibrosis in myelofibrosis, which could also be explained by the immunosuppressive effect of busulfan or6-thioguanine.…”
Section: Discussionmentioning
confidence: 95%
“…Various immunologic abnormalities such as in creased serum antinuclear and antismooth muscle au toantibodies, rheumatoid factor and polyclonal ele vation of immunoglobulin levels have been reported in patients with IMF [21][22][23]. Since the severe refrac tory anemia of the patients responded to the treat ment, and immune complexes of our first patient dis appeared as in the study of Lewis and Pegrum [23], we believe that bolus treatment of méthylprednisolone was effective through its immunosuppressor effect, which should be shown by the study of other cases.…”
Section: Discussionmentioning
confidence: 99%
“…In PNH, in addition to a depressed cellu lar immunity, there is an increase in the im munoglobulin level [10]; antierythrocyte isoantibodies (anti-D, anti-C + D, antiCw), and antileukocyte antibodies [5], In myelofibrosis [14] and leukemia [24] there is experimental evidence of the existence of circulating immune complexes. Our findings provide evidence for the presence of circu lating immune complexes in PNH.…”
Section: Discussionmentioning
confidence: 99%